(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The purpose of the formation of a socially oriented market economy in the country is to improve the welfare of the population, to meet its growing needs, to raise the cultural and spiritual level and to ensure the peaceful coexistence of society. Due to the formation of market relations in our country at the level of society, there are financial difficulties among certain segments of the population. This will be achieved by the state using the funds of the centralized social protection system to solve the problems that have arisen temporarily. Social problems, social protection and social security problems cannot be left alone. The world’s population is growing every year. At the same time, the United Nations is concerned about the growing poverty of the world’s population